To the methodology of the research of the gte turbine blades platformswear - Ivshchenko, L.I.; Pribora, T.I.; Komochkin, N.S.; Sakhnyuk, N.V. (Publishing House of the KarSU named after E.A.Buketov, 2016)
The problem of the gas turbine engine turbine blades platforms wear is discussed. The methodology to solve this problem by defining the processes that occur in platforms is suggested. The object model test and research methods are described. Describes the object modeling techniques and explore patterns of oscillations of the system of coupled oscillations of parts of an aircraft engine turbine. An original setting for the study of the wear of rotor blades was used.
Keywords: wear; platforms; blades; turbines; gas turbine plant